Pelatihan Satuan Pendidikan Aman Bencana (SPAB) di Kota Malang - Sholikin, Nur Wiji; Sholehudin, Arif (Jurnal Al Maesarah, 2026)
This community service activity aims to improve the preparedness of educational units in facing potential disasters through Disaster Safe Education Unit (SPAB) training. The training was conducted in three schools in Malang City, namely SDN Jatimulyo 3, MA Daruttauhid, and SDN Gadang 1, which were selected based on their low levels of vulnerability and preparedness. The method used was a participatory-educational approach through the stages of delivering disaster material, SPAB document preparation workshops, evacuation simulations, and psychosocial support training. The results of the activity showed a significant increase in the understanding and skills of school residents related to disasters, with an average increase in post-test scores of 40–45% compared to the pre-test. Observations and interviews also showed that the training encouraged changes in attitudes and behavior, including readiness to prepare and carry out emergency evacuation procedures. This activity strengthens the theory of contextual learning and community-based disaster education, and provides a practical contribution in the form of an applicable and easily replicable SPAB training model. The involvement of BPBD, IGI, and Dirgantara Rescue also strengthened the quality of the training. This SPAB training is expected to be a strategic model in building a disaster-resilient culture in educational environments.